Research on Experimental Behaviour of Water Hyacinth Ash as Partial Replacement of Cement on Short Column - Murugesh, V.; Thirumurugan, A.; Sadhasivam, M.; Sudharsanan, M. (Advanced Aspects of Engineering Research Vol. 3, 2021)
The present study on investigations of short column concrete under axial loading condition with the substitute for cement by water hyacinth ash (WHA). The strength of the column can be investigated with different proportions of cement replacement by 0% and 10%, of the cement weight for M30.WHA replacement increases to concrete it delays the setting time of concrete and also affect the potency of concrete. A total of five columns consisting of two conventional RCC columns, three RCC column with 10% replacement, was tested. The experimental result reveals that the optimal percentage of addition of WHA to the concrete was found to be 10% with respect to the weight of cement. Results show that WHA is used as a substitute cement substance in concrete. For higher replacement of WHA in cement, the compressive strength and split tensile strength gets decrease.